Association of BMI with total mortality and recurrent stroke among stroke patients: A meta-analysis of cohort studies. (October 2016) - Huang, Keyong; Liu, Fangchao; Han, Xikun; Huang, Chen; Huang, Jianfeng; Gu, Dongfeng; Yang, Xueli
Abstract: Background and aims: Studies of the association between obesity and total mortality and recurrent stroke events have shown contradictory results. Therefore, we aimed to conduct a meta-analysis to examine the association of body mass index (BMI) with total mortality and recurrent stroke events among patients after stroke onset. Methods: We performed an electronic search of PubMed, EMBASE and the Cochrane Library Database, as well as a bibliography review to identify relevant cohort studies published prior to 15th December 2015. Estimates of relative risks (RRs) and corresponding 95% confidence intervals (CIs) comparing underweight, overweight and obese groups with normal weight were pooled using random effects models. Results: In total, 15 studies with 122, 472 stroke patients were eligible for inclusion in the meta-analysis. Compared with the normal weight group, obese stroke patients had a significant decreased risk for total mortality (RR = 0.83, 95% CI, 0.73–0.93, p = 0.002), while underweight patients had a significant increased risk for total mortality (RR = 1.54, 95% CI, 1.31–1.82, p = 3.66 × 10 −7 ). A similar, but not significant, association of BMI categories with recurrent stroke events was also observed. Furthermore, the dose-response meta-analysis identified a nonlinear trend for total mortality and a linear trend for recurrent stroke events, associated with BMI. Conclusions: Our results suggested that obesity may have a protective effect on total mortality and recurrent stroke events among patients with established stroke. Highlights: This meta-analysis comprising 122, 472 stroke patients confirmed the inverse association of BMI with total mortality. A similar association of obesity with recurrent stroke events was observed. A nonlinear dose-response trend for total mortality and a linear trend for recurrent stroke were identified with BMI. Our findings provide evidence for secondary prevention for stroke.